2009
DOI: 10.1007/s00125-009-1553-y
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes regulates mitochondrial biogenesis and fission in mouse neurons

Abstract: Aims/hypothesis Normal mitochondrial activity is a critical component of neuronal metabolism and function. Disruption of mitochondrial activity by altered mitochondrial fission and fusion is the root cause of both neurodegenerative disorders and Charcot-Marie-Tooth type 2A inherited neuropathy. This study addressed the role of mitochondrial fission in the pathogenesis of diabetic neuropathy. Methods Mitochondrial biogenesis and fission were assayed in both in vivo and in vitro models of diabetic neuropathy. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
118
2
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 52 publications
(67 reference statements)
11
118
2
4
Order By: Relevance
“…Zorzano et al (2009) therefore hypothesized that these mitochondrial dynamics proteins play a key role in mitochondrial dysfunction in obesity or in type 2 diabetes and may participate in the development of insulin resistance. This concept is supported by recent studies in muscle (Zorzano et al, 2009) and neurons (Edwards et al, 2010). …”
Section: Transcriptional Regulation Of Mitochondrial Oxidative Capacisupporting
confidence: 58%
“…Zorzano et al (2009) therefore hypothesized that these mitochondrial dynamics proteins play a key role in mitochondrial dysfunction in obesity or in type 2 diabetes and may participate in the development of insulin resistance. This concept is supported by recent studies in muscle (Zorzano et al, 2009) and neurons (Edwards et al, 2010). …”
Section: Transcriptional Regulation Of Mitochondrial Oxidative Capacisupporting
confidence: 58%
“…Furthermore, we found that acute downregulation of Hsp60 via bilateral injection of a lentivirus containing shRNA against HSP60 into the hypothalamus caused insulin resistance, indicating that hypothalamic mitochondrial dysfunction can cause insulin resistance. An alteration in mitochondrial dynamics, such as increased mitochondrial fission, has been shown to cause oxidative stress in skeletal muscle and neurons (41) and insulin resistance in obese and diabetic mice (42). On the other hand, in hepatocytes, insulin signaling is sufficient to induce HSP60 (43).…”
Section: Discussionmentioning
confidence: 99%
“…Studies are already under way in our laboratory to demonstrate that hyperglycemia induces an increase in the number of sites where BrdU is incorporated into mtDNA of DRG neurons (Edwards et al 2010). The use of EdU as a marker for mtDNA replication and dual labeling mtDNA replication with BrdU and EdU will allow for pulse labeling paradigms to answer time course or subcellular compartmentalization questions that could not be addressed with a single label.…”
Section: Discussionmentioning
confidence: 99%